Development of Metformin and Glimepiride Analysis Methods Using TLC-Spectrofluorometry - Adlina, Salsabila; Ibrahims, Slamet; Permana, Benny (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder disease. DM presents in two main types 1and 2. Type 2 DM was caused by genetic and lifestyle which was the biggest contributor to DMcases. Many patients with type 2 DM treated with combination therapy using Fix Dose Combination(FDC) preparation to increase patients compliance and therapeutic effect. FDC preparations containedmetformin and glimepiride. Assay of these combination was not found in compendial. A rapid,simple, specific method analysis of metformin and glimepiride has been developed in this riset usingTLC-spectrofluorometry. Metformin and glimepiride content in tablet were determined by the TLC-spectrofluorometry using dansyl chloride as derivatization agent under alkali conditions. In the TLCmethod, metformin and glimepiride were dissolved with methanol and gives Rf values of 0.52 and0.70, respectively in system containing silika gel GF254 as stationary base and methanol:water: glacialasetic acid (6:4:0.25) as developing solvent. TLC results were scraped off and reacted using dansylchloride 0.1% then fluorescence intensity measurements were carried out at emission wavelength 483nm for metformin and 489 nm for glimepiride. Method validation is done by determining linearity,accuracy, precision, Limit Of Detection (LOD) and Limit Of Quantization (LOQ).